Polyhydroxylated sulfated steroids derived from 5α-cholestanes as antiviral agents against herpes simplex virus - Pujol, Carlos Alberto (2016)
Twelve polyhydroxylated sulfated steroids synthesized from a 5α-cholestane skeleton with different substitutions in C-2, C-3 and C-6 were evaluated for cytotoxicity and antiviral activity against herpes simplex virus (HSV) by a virus plaque reduction assay. Four compounds elicited a selective inhibitory effect against HSV. The disodium salt of 2β,3α-dihydroxy-6E-hydroximine-5α-cholestane-2,3-disulfate, named compound 7, was the most effective inhibitor of HSV-1, HSV-2 and pseudorabies virus (PrV) strains, including acyclovir-resistant variants, in human and monkey cell lines. Preliminary mechanistic studies demonstrated that compound 7 did not affect the initial steps of virus entry but inhibited a subsequent event in the infection process of HSV.